Revitalizing the Role of “Bundo Kanduang” in Forging Radicalism and Extremism in Minangkabau - Yanti, Novia; Lindra, Afni; Indria, Anita; Hanton, Hanton (Ahlussunnah: Journal of Islamic Education, 2025)
It is highly expected that Bundo Kanduang will return to its proper role in carrying out its duties. Seeing the many problems that arise among teenagers, especially Minangkabau girls. This study aims to analyze the role of Bundo Kanduang in revitalization in accordance with the development of the times as we experience it today. This study examines the literature review sourced from various literatures, both books, journals, or published articles. The results of this literature finding the author will find Conclusions and Solutions about the revitalization of the role of Bundo Kanduang in the current era facing radicalism and extremism. The results of the analysis found that the role of Bundo Kanduang is adjusted to the 12th Contribution, in this Contribution found rules that are in accordance with the sharia and philosophy of Minangkabau. The implications of this study can be the beginning of the discovery of an analysis of the revitalization of the role of Bundo Kanduang in examining different problems and issues.